In-Depth Characterization and Functional Analysis of Clonal Variants in a Mycobacterium tuberculosis Strain Prone to Microevolution - Navarro, Yurena; Pérez-Lago, Laura; Herranz, Marta; Sierra, Olalla; Comas, Iñaki; Sicilia, Javier; Bouza, Emilio; García de Viedma, Darío (Frontiers in Microbiology, 2017)
The role of clonal complexity has gradually been accepted in infection by Mycobacterium tuberculosis (MTB), although analyses of this issue are limited. We performed an in-depth study of a case of recurrent MTB infection by integrating genotyping, whole genome sequencing, analysis of gene expression and infectivity in in vitro and in vivo models. Four different clonal variants were identified from independent intrapatient evolutionary branches. One of the single-nucleotide polymorphisms in the variants mapped in mce3R, which encodes a repressor of an operon involved in virulence, and affected expression of the operon. Competitive in vivo and in vitro coinfection assays revealed higher infective efficiency for one of the clonal variants. A new clonal variant, which had not been observed in the clinical isolates, emerged in the infection assays and showed higher fitness than its parental strain. The analysis of other patients involved in the same transmission cluster revealed new clonal variants acquired through novel evolutionary routes, indicating a high tendency toward microevolution in some strains that is not host-dependent. Our study highlights the need for integration of various approaches to advance our knowledge of the role and significance of microevolution in tuberculosis.